WATER TURBIDITY MONITORING SYSTEM AND RICE FIELD IRRIGATION DISCHARGE DOOR CONTROL USING BLYNK - Dzakiya Nur Yuniar; Fikra Titan Syifa; Nur Afifah Zen (Journal of Electronic and Electrical Power Applications, 2022)
The research objective is to design an IoT-based rice field irrigation turbidity monitoring system, where later farmers can monitor water turbidity and control the Internet of Things (IoT) through Turbidity sensor processing and the ESP8266 module produced by Relay and cloud Blynk processing. The research flow starts from a literature search, the software design process compiles program scripts for each component that has been programmed through the Arduino IDE application, then creates Blynk which is used to monitor or monitoring the turbidity of irrigation water in real time. After designing the hardware and software, the next stage is system testing, if there are constraints and the results are not appropriate, then the hardware and software design is carried out again until the test is successful and the data results are appropriate, then proceed to the next stage of making the test data results. The research results of the Water Turbidity Monitoring System and Rice Irrigation Ditch Control Using Blynk have been successfully designed and functioning properly. The turbidity sensor works well with sensor readings that pass the range of 10 to 70. If the sensor value is less than 10, the water is detected as clean, but the value is more than 70, then the water is detected as cloudy or dirty. Findings Quality of service (QoS) research shows unsatisfactory or poor results in the delay, packet loss, and throughput components, which are caused by poor internet connectivity.